The Determinants of Family Support of Lung TB Patients in Consuming Anti Tuberculosis Medicine in Polonia Health Center Medan - Asriwati Asriwati; Poppy Indah Tristiyana (Humanistic Network for Science and Technology (HNST), 2020)
Tuberculosis treatment requires a relatively long time with two stages, namely the internship stage and the advanced stage. The number of drugs that must be taken and the toxicity and side effects of the drug can be a barrier in the completion of therapy for tuberculosis patients. Tackling tuberculosis through the provision of anti-tuberculosis drugs (OAT) in the DOTS Directly Observation Treatment Strategy (DOTS). Compliance with TB drugs is not done regularly, not according to the time of treatment, and the use of anti-tuberculosis (OAT) drugs will not adequately cause resistance to OAT or what is called Multi Drugs Resistance (MDR). This study aims to determine the factors that influence family support in patients with pulmonary TB in taking anti-tuberculosis drugs in Polonia Health Center Medan in 2019. The type of research used in this study is an analytical survey with a cross-sectional study design. The population was all Category I Lung Tuberculosis patients who were registered at the Polonia Health Center Medan from October to November 2019. The total sampling was 48 samples. In this study, bivariate and multivariate test analyses were performed using multiple logistic regression formulas. The result showed that there is an influence of patient's family support in taking anti-tuberculosis drugs, there is an influence of taking patient's medication in taking anti-tuberculosis drugs in the Polonia Health Center Medan in 2019. The family suggested involving in taking anti-tuberculosis drugs. Keywords: tuberculosis; family support; supervision of taking medication; patients